2020
DOI: 10.1038/s41598-020-71584-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of right ventricular performance and impact of continuous positive airway pressure therapy in patients with obstructive sleep apnea living at high altitude

Abstract: Obstructive sleep apnea syndrome (OSAS) can lead to alterations in right ventricular (RV) performance and pulmonary vascular haemodynamics. Additionally, altitude-related hypoxia is associated with pulmonary vasoconstriction, and the effect of high-altitude on the pulmonary circulation in OSAS patients can be further altered. We sought to assess alterations in RV morphology and function in OSAS patients living at high altitude by way of 2-dimensional speckle tracking echocardiography (2D-STE), real-time 3- dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…These findings may be related to differences in baseline characteristics of the population study, such as obesity, BP and glucose regulation, as well as duration of CPAP therapy (hours per night, total duration of therapy during follow‐up) and compliance to therapy. Of note, our meta‐analysis shows that LVEF significantly increased after CPAP therapy; this parameter was in the normal range independently of OSA severity in the majority of studies 18–24 and LVEF deterioration from mild, to moderate, and severe OSA was only reported by Hammerstingl and coworkers 17 These authors reported that LVEF improved in patients with moderate and severe OSA, but not in mild OSA; in other studies, LVEF values before and after CPAP treatment have been reported in the OSA group as a whole 19,21 …”
Section: Discussionmentioning
confidence: 67%
“…These findings may be related to differences in baseline characteristics of the population study, such as obesity, BP and glucose regulation, as well as duration of CPAP therapy (hours per night, total duration of therapy during follow‐up) and compliance to therapy. Of note, our meta‐analysis shows that LVEF significantly increased after CPAP therapy; this parameter was in the normal range independently of OSA severity in the majority of studies 18–24 and LVEF deterioration from mild, to moderate, and severe OSA was only reported by Hammerstingl and coworkers 17 These authors reported that LVEF improved in patients with moderate and severe OSA, but not in mild OSA; in other studies, LVEF values before and after CPAP treatment have been reported in the OSA group as a whole 19,21 …”
Section: Discussionmentioning
confidence: 67%
“…There are growing data supporting the increase in RV dysfunction among patients with obesity 26,27 and in patients with obstructive sleep apnea, although initiation of continuous positive airway pressure has been demonstrated to improve RV structure and function in the latter. 28–30 In addition, we observed that the presence of moderate-or-greater tricuspid regurgitation was associated with a lower PAPi. Significant tricuspid regurgitation leads to RV dilation through increased diastolic volume, and progressive RV dilation/dysfunction and a lower cardiac output in these patients have been shown to be associated with mortality.…”
Section: Discussionmentioning
confidence: 65%
“…Chu et al showed that six-month CPAP therapy caused a significant increase of global and longitudinal strain. Moreover, they observed a decrease of AHI and duration of desaturation <90% [30].…”
Section: Discussionmentioning
confidence: 93%